Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5530/fra.2017.2.29
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Anti-oxidant Activity in Methanolic Extracts of five Pogostemon Spciece

Abstract: A multifaceted peer reviewed journal in the field of Free Radicals and Antioxidants www.antiox.org | www.phcog.net Original Article INTRODUCTIONPlants have provided with all in terms of shelter, clothing, food, flavours and fragrances and medicine properties. Plants have formed the basis of complicated traditional medicine systems that have been in continuation for thousands of years to provide new remedies. The Lamiaceae contains about 236 genera and 6,900 to 7,200 species, 1 in this Pogostemon is one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The results showed that the antioxidant activities of the Iphiona aucheri stem methanolic extract and its different fractions are concentration dependent. Similar results were observed in previous studies of Leucas aspera (Willd) link (Annapandian and Rajagopal 2017) and Pogostemon species (Kaliyappan et al 2017).…”
Section: Resultssupporting
confidence: 92%
“…The results showed that the antioxidant activities of the Iphiona aucheri stem methanolic extract and its different fractions are concentration dependent. Similar results were observed in previous studies of Leucas aspera (Willd) link (Annapandian and Rajagopal 2017) and Pogostemon species (Kaliyappan et al 2017).…”
Section: Resultssupporting
confidence: 92%